Komunikasi Dakwah Melalui Kegiatan Pengajian Subuh di Masjid untuk Menghindari Kenakalan Remaja di Zaman Sekarang - Siti Maesyaroh,, Syarah; Santika, Mira; Sevtiani, Lestari; Fauziah, Nurul (CV RIFAINSTITUT, 2025)
The increase in juvenile delinquency in the modern era requires an effective preventive approach through mosque-based da'wah communication. This study aims to determine the influence of dawn recitation on religious understanding and character formation of adolescents, identify da'wah messages for the prevention of delinquency, and assess the response and behavior change of adolescents. The qualitative research method with a case study approach was applied to 5-10 adolescent worshippers and 2-4 da'i or mosque administrators. Data was collected through in-depth interviews, participatory observations, and documentation. The results of the study show that dawn recitation is effective in improving religious understanding and shaping the character of adolescents through da'wah materials that are relevant to contemporary problems. Dialogical-participatory methods, storytelling, and personal approaches have succeeded in attracting the interest of adolescents. Significant impacts can be seen in increasing religious awareness, establishing self-control, social selectivity, and reducing deviant behavior. Dawn recitation has proven to be a comprehensive solution to prevent juvenile delinquency through continuous spiritual, cognitive, and behavioral transformation.